Us Experience of Asset Securitization - Akhmedov Akbarali Sultanmurodovich (International Journal on Integrated Education, 2022)
The article studies theoretical and practical approaches to securitization of assets. The analysis of securitization of assets in the United States. The problems are studied and conclusions on them are drawn and the ways of the decision on introduction of processes of securitization of assets in Uzbekistan are offered.